Protection for Housing Loan Consumers in Building Insurance toward the Risk of Natural Disaster Loss during the Construction Process - Ryo Crysna Ramli Koro (Volksgeist: Jurnal Ilmu Hukum dan Konstitusi, 2022)
This study's purpose is to examine and analyze legal protection for consumers who have housing loans and to examine and analyze the liability of insurance companies against the risk of loss due to the length of the development process. This research uses a normative juridical method whose research source is library data. This is descriptive-analytic research, which describes something in words or sentences, and then the categories are separated to obtain conclusions. Its approach is a legal approach and a conceptual approach. Its primary legal materials are Law Number 8 of 1999 concerning Consumer Protection, Law Number 40 of 2014 concerning Insurance, and Law Number 10 of 1998 concerning Banking. As a result, this study concluded that there is legal protection for consumers who have housing loans in the event of a natural disaster risk. Namely, consumers who own housing loans have bound themselves to housing developers, banks, and insurance companies to transfer all unexpected risks that occur in the future, such as natural disasters. The transfer of risk in the form of guaranteeing the property and goods belonging to consumers of housing loans is the government's responsibility because its role as an institution that protects the community is very important and does not only refer to the law but is the obligation. In this case, the government does not only plays role as a policy initiator but also as a party that overshadows the community. Even citizens, as set out in the second precepts of the Pancasila, have the responsibility.